1979
DOI: 10.1063/1.437751
|View full text |Cite
|
Sign up to set email alerts
|

The spin-forbidden dissociation–recombination reaction SO3?SO2+O

Abstract: Rate constants for the spin-forbidden dissociation process SO3+Ar→SO2+O+Ar have been measured in shock waves between 1700 and 2500 K. The results are compared with data on the low temperature (200–400 K) recombination reaction. The analysis in terms of unimolecular reaction rate theory allows for a determination of the threshold energy of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 14 publications
5
59
0
Order By: Relevance
“…From an assessment of each contribution, we estimate the overall uncertainty in k 1b to be a factor of 2. Figure 8 compares the data for the thermal dissociation rate of SO 3 with the only other measurements of this reaction, the shock tube study of Astholz et al 10 While the present study involved nitrogen as collision partner, Astholz et al conducted their experiments in argon. The two sets of data appear to be consistent, but a direct comparison is difficult due to the differences in the temperature regime and bath gas.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…From an assessment of each contribution, we estimate the overall uncertainty in k 1b to be a factor of 2. Figure 8 compares the data for the thermal dissociation rate of SO 3 with the only other measurements of this reaction, the shock tube study of Astholz et al 10 While the present study involved nitrogen as collision partner, Astholz et al conducted their experiments in argon. The two sets of data appear to be consistent, but a direct comparison is difficult due to the differences in the temperature regime and bath gas.…”
Section: Resultsmentioning
confidence: 95%
“…14 The results from the flow reactor study of Mueller et al 7 and the shock tube study of Hwang et al 15 on the reaction are not included, since they were obtained at higher pressures. The hightemperature data of Astholz et al 10 and Smith et al 12 are shown, even though they relate to argon as a bath gas. The values of k 1 [ The solid lines are the rate constant at 1 atm, while the dashed lines represent the low-pressure limit.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations